Functional Significance of Probiotic Bacterial Interactions with Milk Fat Globules in a Human Host - Withanage Prasadini Wasana; Mark Waterland; David W. Everett; Caroline Thum (Microorganisms)
Dairy products often serve as matrices for delivering probiotic bacteria to humans through the diet; however, little is known about the impact of milk fat globules on the growth and survival of probiotic microorganisms. This review discusses current knowledge on the structure and functionality of the milk fat globule membrane (MFGM) and the structural components contributing to the mechanisms of interactions with probiotic bacteria. We analyzed studies published between 2001 and 2025 with reference to earlier foundational research on probiotics and MFGM structure to explore the functional significance of MFGM–probiotic interactions. Recent research indicates that the effects of MFGM interaction with bacteria are species-specific and may influence probiotic activity in the host, including enhancing probiotic viability during intestinal transit and modulating probiotic colonization. In general, research findings suggest that the MFGM holds potential for use as a probiotic carrier to the gut with beneficial health consequences.